Melanocytic nevi. II. Acquired nevus cell nevi. - Bonifazi, E.; Ferrante, M.R.; Bellomo, G.; Chieco, P. (European Journal of Pediatric Dermatology, 2002)
Melanocytic nevi are due to a benign, thus self-limiting, proliferation of melanocytes. The proliferation can give raise to a flat (Fig. 1091) or raised lesion. The pathological findings of the former consist of groups or nests of melanocytes level with the dermal-epidermal junction (Fig. 1092). This is why it is named junctional nevus. On the other hand, intradermal nevus is clinically raised and characterized, from a pathological point of view, by the presence in the dermis of melanocytes and nevus cells (Fig. 1094). However, intradermal nevus is often preceded by a junctional nevus, as supported by a junctional halo at its periphery in many cases (...).